Securitisation : for issuers, arrangers and investors - Fisher, Mark; Shaw, Zoe (London : Euromoney books, 2003)
Designed as a practical introduction to the key principles of securitization. This edition updates the 1996 edition and includes important new materials on the topic.
oif 28/08/15
Loans
Keywords: Securities; Securitization; Asset-backed financing; Corporations